Icaritin induces lytic cytotoxicity in extranodal NK/T-cell lymphoma - Wu, Ting (J Exp Clin Cancer Res, 2015)
BACKGROUND: Extranodal NK/T-cell lymphoma (ENKL) is an aggressive hematological malignancy associated with Epstein–Barr virus (EBV) infection. It is often resistant to conventional chemotherapy and has a poor prognosis. Icaritin, a compound derived from Chinese herbal medicine, Herba Epimedii, has been reported to exert antitumor effects on a variety of cancer cell lines. In the present study, we investigated the cytotoxic effects of Icaritin on the two EBV-positive ENKL cell lines SNK-10 and SNT-8, along with the underlying molecular mechanisms. METHODS: ENKL cell lines SNK-10 and SNT-8 were exposed to different concentrations of Icaritin for the indicated time. Treated cells were analyzed for cell proliferation, cell cycle, and cell apoptosis. Phosphorylation of Stat3 and Akt proteins in signaling pathways and the EBV-encoded LMP1 proteins were measured by Western blot. Expression of EBV genes was assessed by Real-Time PCR. RESULTS: Our results showed that Icaritin dose-dependently inhibits ENKL cell proliferation and induces apoptosis and cell cycle arrest at G(2)/M phase. Additionally, Icaritin upregulates Bax, downregulates Bcl-2 and pBad, and activates caspase-3 and caspase-9. The anti-proliferative and pro-apoptotic effects of Icaritin are likely mediated by inhibition of Stat3 and Akt pathways through LMP1 downregulation. Importantly, Icaritin induces EBV lytic gene expression in ENKL cells, and the combination of Icaritin and the antiviral drug ganciclovir (GCV) is more effective in inducing ENKL cells apoptosis than Icaritin or GCV alone. CONCLUSIONS: These findings indicate that EBV-targeted approaches may have significant therapeutic potential for ENKL treatment.